Minimizing Delays in the Jordanian Construction Industry by Adopting BIM Technology - Btoush, Mohammed; Ahmad Tarmizi, Haron (IOP Publishing, 2017)
The Jordanian construction industry plays a significant role and contributes immensely to the gross domestic product (GDP) of the economy. However, the Jordanian public work and housing ministry and most industry players including engineers and contractors have reported that most of the projects experience delays which lead time and cost overruns, and extra efforts. The main causes of delays identified by researchers include poor scheduling and planning, change orders, site conditions, weather, late deliveries, incompetent technical staff. To address these challenges, the implementation of building information modelling (BIM) is paramount. This paper presents BIM as a powerful tool for reducing delays in Jordan construction projects. The paper focuses on two main parts; the first part involves the identification of the major causes of delays, and the second part is to accurately outline the roles and responsibilities of BIM specialist in construction projects. Finally, the paper matches the roles and responsibilities of BIM specialist and the causes of delays, and how the delays are addressed through BIM specialist.